Changes of Health-Related Quality of Life Within the 1st Year After Stroke–Results From a Prospective Stroke Cohort Study - Kainz, Anabelle; Meisinger, Christa; Linseisen, Jakob; Kirchberger, Inge; Zickler, Philipp; Naumann, Markus; Ertl, Michael (Frontiers in Neurology, 2021)
Introduction: As prospective data on long-term patient-reported outcome measures (PROMs) to assess Health related Quality of Life (HRQoL) after stroke are still scarce, this study examined the long-term course of PROMs and investigated influential factors such as recanalization therapies. Materials and Methods: A total of 945 (mean age 69 years; 56% male) stroke patients were enrolled with a personal interview and chart review performed at index event. One hundred forty (15%) patients received thrombolysis (IVT) and 53 (5%) patients received endovascular therapy (ET) or both treatments as bridging therapy (BT). After 3 and 12 months, a follow-up was conducted using a postal questionnaire including subjective quality of life EQ-5D-5L (European Quality of Life 5 Dimensions). At all time-points, Modified Rankin Scale (mRS) was additionally used to quantify functional stroke severity. Differences between therapy groups were identified using post-hoc-tests. Linear and logistic regression analyses were used to identify predictors of outcomes. Results: Recanalization therapies were associated with significant improvements of NIHSS (National Institutes of Health Stroke Scale [regression coefficient IVT 1.21 (p = 0.01) and ET/BT 7.6; p = 0.001] and mRS (modified Rankin Scale) [regression coefficient IVT 0.83; p = 0.001 and ET/BT 2.0; p = 0.001] between admission and discharge compared to patients with stroke unit therapy only, with a trend toward improvement of EQ-5D after 12 months [regression coefficient 4.67 (p = 0.17)] with IVT. HRQoL was considerably impaired by stroke and increased steadily in 3- and 12-months follow-up in patients with (mean EQ-5D from 56 to 68) and without recanalization therapy (mean EQ-5D from 62 to 68). In severe strokes a major and significant improvement was only detected during period of 3 to 12 months (p = 0.03 in patients with and p = 0.005 in patients without recanalization therapy). Conclusions: Despite significant and continuous improvements after stroke the HRQoL after 12 months remained below the age-matched general population, but was still unexpectedly high in view of the accumulation of permanent disabilities in up to 30% of the patients. Especially in severe strokes, it is important to evaluate HRQoL beyond a 3-months follow-up as improvements became significant only between 3 months and 1 year.